2020
DOI: 10.3390/ijms21186541
|View full text |Cite
|
Sign up to set email alerts
|

The Beneficial Effects of Morusin, an Isoprene Flavonoid Isolated from the Root Bark of Morus

Abstract: The root bark of Morus has long been appreciated as an antiphlogistic, diuretic and expectorant drug in Chinese herbal medicine, albeit with barely known targets and mechanisms of action. In the 1970s, the development of analytic chemistry allowed for the discovery of morusin as one of 7 different isoprene flavonoid derivatives in the root bark of Morus. However, the remarkable antioxidant capacity of morusin with the unexpected potential for health benefits over the other flavonoid derivatives has recently sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 87 publications
(150 reference statements)
0
19
0
Order By: Relevance
“…The present analysis sheds light on the artonin group of prenylated compounds and points out the prenylflavone Art-E as an interesting anticancer natural product. Art-E displays a range of pharmacological activities, chiefly antioxidant and anti-inflammatory effects, similar to those reported with the analogous isoprene flavonoid morusin (Choi et al 2020). It is a potent anticancer agent, inspiring for the design and development of novel anticancer agents.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…The present analysis sheds light on the artonin group of prenylated compounds and points out the prenylflavone Art-E as an interesting anticancer natural product. Art-E displays a range of pharmacological activities, chiefly antioxidant and anti-inflammatory effects, similar to those reported with the analogous isoprene flavonoid morusin (Choi et al 2020). It is a potent anticancer agent, inspiring for the design and development of novel anticancer agents.…”
Section: Discussionmentioning
confidence: 68%
“…The structural analogy between morusin and Art-E deserves further attention. Morusin has been much more studied than Art-E as an anticancer agent but also for its antiviral and antidiabetic effects (Choi et al 2020;Kim et al 2021). The in vitro and in vivo anticancer effects of morusin have been extensively characterized and the compound appeared promising against cancer stem cells (Zoofishan et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Morusin (Fig. 1a) is one of the main active substances isolated from mulberry bark, which was proved to have antitumor, anti-inflammatory, and antifungal activities [13][14][15]. Combined with previous researches, we found that Morusin could inhibit the progression of human osteosarcoma by means of the phosphatidylinositol 3′-kinase(PI3K)-Akt signaling pathway [16].…”
Section: Introductionmentioning
confidence: 64%
“…This is the first time Table 1 The screened top 20 differential metabolites of engineered B. subtilis and E. coli during co-fermentation a The card value standard for screening differential metabolites is p < 0.05 and VIP > 1.0 that turanose production has been found in the co-culture system of B. subtilis and E. coli. It is also the first time that the flavonoid morusin is found in the co-cultivation process of recombinant strains, and it has potential medical application value (Choi et al 2020).…”
Section: Differential Metabolites Analysismentioning
confidence: 99%